Multiple Access Communications 4th International Workshop, MACOM 2011, Trento, Italy, September 12-13, 2011. Proceedings - Sacchi, Claudio; Bellalta, Boris; Vinel, Alexey; Schlegel, Christian; Granelli, Fabrizio; Zhang, Yan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Workshop on Multiple Access Communications, MACOM 2011, held in Trento, Italy, in September 2011. The 21 full papers papers presented were carefully reviewed and selected from more than 40 submissions. They are divided in topical sections on cognitive radio; MAC protocols; communications theory; special session on MAC protocols for WSNs; system analysis and scheduling; and queuing systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Software Engineering; Data Encryption